Critical Review and Benchmark Proposal on FE Modeling for Patch Loading Resistance of Slender Steel Plate Girders in Launched Bridges - Marck Anthony Mora Quispe (Buildings, 2025)
The patch loading resistance of slender steel plate girders is a critical factor in the design of launched steel and composite steel–concrete bridges. Traditional design methods enhance patch loading resistance through various stiffening techniques, with contributions typically estimated via code expressions calibrated on experimental data that do not always reflect the complexities of full-scale bridge applications. Finite Element (FE) modeling offers a more realistic alternative, though its practical application is often hindered by modeling uncertainties and nonlinearities. To bridge this gap, this paper introduces an advanced FE modeling approach. It provides a comprehensive description of an FE model that accurately predicts both the load–displacement behavior and the patch loading resistance. The model is benchmarked against a broad set of experimental tests and systematically investigates the effects of key modeling parameters and their interactions—material stress–strain law, boundary condition representation, stiffness of the load introduction area, initial geometric imperfections, and solving algorithms. Key findings demonstrate that a bilinear elastoplastic material model with hardening is sufficient for estimating ultimate resistance, and kinematic constraints can effectively replace rigid transverse stiffeners. The stiffness of the load application zone significantly influences the response, especially in launched bridge scenarios. Initial imperfections notably affect both stiffness and strength, with standard fabrication tolerances offering suitable input values. The modified Riks algorithm is recommended for its efficiency and stability in nonlinear regimens. The proposed methodology advances the state of practice by providing a simple yet reliable FE modeling approach for predicting patch loading resistance in real-world bridge applications, leading to safer and more reliable structural designs.